Effects of passive computer use time and non-computer work time on the performance of electronic activity monitoring. - Hwang Y; Chen Y; Yeh J; Liang H (Ergonomics, 2010)
This study aimed to examine the effects of passive and non-computer work time on the estimation of computer use times by electronic activity monitoring. A total of 20 subjects with computers were monitored for 3 h. Average relative error for total computer use time estimation was about 4%, given that non-computer work time was 20% of the 3-h monitored period. No significant impact of passive computer use time was found in this study. Noncomputer work time of 40% or less is suggested as criteria for the application of electronic activity monitoring to ensure reliability in the physical work loading assessment. Statement of Relevance: This research studied the criteria of non-computer work time for the appropriate use of electronic activity monitoring to ensure reliability in the assessment of physical work loading. It is suggested that it should be set to 40% or less of the 3-h monitoring period.